STUDI KODE ETIK KONSELING MULTIKULTURAL - Erny Indaha Zulfa; Suryadi Suryadi (INSTITUT AGAMA ISLAM NEGERI METRO, 2021)
Multicultural counseling is a relationship that is built between the counselor and the counselee, but both of them have different cultures, so it requires some special techniques in order to successfully achieve the goals of the counseling itself. One of the successes that can be achieved during counseling is the creation of a good relationship between the counselor and the counselee. But behind it all a counselor must understand the characteristics of the counselee's culture. As for certain characteristics or characteristics. The characteristics of cross-cultural counselors are: having cultural awareness, understanding the characteristics of counseling in general, showing an attitude of empathy, etc. One of the factors in the failure of the cross-cultural counseling process is that the perception held by the counselor is not the same as the perception held by the counselee. For this reason, a counselor must develop skills in cross-cultural counseling to avoid cultural barriers and biases in the counseling process.